Pengaruh Literasi Keuangan, Digital Marketing, dan Penggunaan Sistem Informasi Akuntansi terhadap Kinerja UMKM di Kota Surabaya - Silvi Kurnia; Hwihanus (Journal of Economics, Management, and Accounting, 2026)
This study examines the influence of financial literacy, digital marketing, and the use of accounting information systems on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City. A quantitative survey approach was employed involving 150 MSME owners selected through purposive sampling. Primary data were collected using structured questionnaires and analyzed with multiple linear regression. The findings indicate that financial literacy, digital marketing, and the use of accounting information systems each have a positive and significant effect on MSME performance. Simultaneously, the three variables significantly affect MSME performance, with a coefficient of determination (R²) of 0.682, indicating that 68.2% of the variation in MSME performance is explained by the proposed model. The findings emphasize the importance of strengthening financial capabilities, expanding digital marketing adoption, and improving the implementation of accounting information systems to enhance MSME competitiveness in the digital transformation era.